2015
DOI: 10.1177/0021998315591300
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the vol% SiC on properties of pressureless Al2O3/SiC nanocomposites

Abstract: Al 2 O 3 /SiC nanocomposites were prepared by pressureless sintering with micron-sized Al 2 O 3 powders whose average ranged 5 mm in d 50 and nano-sized SiC powders whose average ranged 80 nm in d 50 as raw materials. The combined powders were then ball-milled in iso-propanol alcohol and then, the slurry was freeze granulated. Compressed samples were prepared by cold isostatic pressing of the granules. Pressureless sintering was carried out in an argon atmosphere at 1750 C for 4 h. The physical and mechanical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Hence, increasing compressive stresses around SiC particles enhanced the fracture toughness of HfB 2 –SiC–VSi 2 composite. These results were supported by other researchers 45 – 49 .…”
Section: Resultssupporting
confidence: 91%
“…Hence, increasing compressive stresses around SiC particles enhanced the fracture toughness of HfB 2 –SiC–VSi 2 composite. These results were supported by other researchers 45 – 49 .…”
Section: Resultssupporting
confidence: 91%
“…They demonstrated that the addition of SiC up to 20 vol% enhances the fracture toughness of the composite. In a similar study, Ghadami et al 51 investigated the reinforced composite by SiC. They discovered the fracture toughness value diminished due to using the reinforcement more than a specific proportion.…”
Section: Resultsmentioning
confidence: 99%